Substantiation of determination of strength performance of coarse-grained media by the oblique shear method - Shabaev Sergey (EDP Sciences, 2021)
The constantly increasing loads of vehicles predetermine the search for ways to improve both design methods, technological processes and the search for ways to improve the quality of road construction materials. The increasing volumes of open-pit coal mining require finding ways to improve the haul roads of open-pit coal mines. Thus, a qualitatively new approach is needed to determine the strength performance of coarse-grained media. In this work, it is proposed to determine the strength performance of granular media by the oblique shear method, since today there is no design method to determine the strength performance of coarse-grained media. The proposed design of the advanced oblique shear apparatus makes it possible to determine the strength performance of pre-compacted coarse-grained media with a particle size of up to 20-30 mm. To avoid the effect of keyways and chaotic results, the optimum clearance between the upper and the lower holders should be 0.3 times the maximum particle size.